A multilevel analysis of the influence of neighborhood- and individual-level socioeconomic factors on smoking among South African adults - Ayo-Yusuf, Olalekan Abdulwahab (University of Pretoria, 2015)
Dissertation (MPH)--University of Pretoria, 2015.